Humanistic education and Participatory Budget - Possible Application in Mirandela and Bragança Teaching Units (Research, Society and Development, 2021)
The present study aimed to analyze the application of the Participatory School Budget (OPE) in two school units in Portugal, the Carvalhais Professional School of Agriculture in Mirandela and the Emídio Garcia School Grouping in Braganza, more precisely, the application of the OPE as a teaching tool within the precepts of humanistic education, omnilateral, based on classical authors of this pedagogy: Marx, Gramsci and Freire. In the context of the paradigm, qualitative, conducted a study of multiple case with the application of interviews semistructured one representative from each, with the objective of characterize your institution regarding the use of the OPE as an educational tool in the framework of humanistic education. It was observed that the OPE is a program of government of the country with the interest to be educational principle, however does not present humanistic bias in its application. Thus, it is expected that the OPE can be applied in an omnilateral bias to all students of the schools involved.